Pesantren dan Pluralisme: Upaya Modernisasi Pendidikan Pesantren Menuju Masyarakat Madani - Muhammad Muntahibun Nafis (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2015)
Pesantren is one of the indigenous institutions of religious education in Indonesia that still exists until recently. Therefore, its role in constructing and developing society as its essential duties is always questioned. However, at least, its sustainable indicates that it fits to fulfill and dialogue with the dynamics society. In other words, it can be regarded as an institution that does not only successfully anticipate, receipt and adopt social developments but also integrates them within its essential tradition and values. This paper just focuses on how pesantren develops its values and tradition to respect plurality. As a result, pesantren has some philosophies and practices supporting in realizing multicultural and plural societies. In this sense, we still have great hope to pesantren roles in developing civilized society